+0  
 
+6
500
2
avatar

Was kommt bei:

 

x³y² * (-xy³) raus?

 

Bitte mit Rechenweg

 25.09.2015

Beste Antwort 

 #2
avatar+14537 
+7

Hallo,

 

\(x^3y^2*(-xy^3)=-x^4y^5\)

 

Gruß radix smiley !

 

\((+)*(-)=(-)\)

 

\(x^3*x=x^4\)

 

\(y^2*y^3=y^5\)

 25.09.2015
 #1
avatar+14537 
+3

Hallo,

 

\(x^3y^2*(-xy^3)=-x^4y^5\)

 

Gruß radix smiley !

 25.09.2015
 #2
avatar+14537 
+7
Beste Antwort

Hallo,

 

\(x^3y^2*(-xy^3)=-x^4y^5\)

 

Gruß radix smiley !

 

\((+)*(-)=(-)\)

 

\(x^3*x=x^4\)

 

\(y^2*y^3=y^5\)

radix 25.09.2015

70 Benutzer online

avatar
avatar
avatar
avatar
avatar